The Educational Methodology of K.H. Ahmad Dahlan: Relevance and Impact on Developing Excellence in Human Resources within the Contemporary Era: (Metodologi Pendidikan K.H. Ahmad Dahlan: Relevansi dan Dampaknya terhadap Pengembangan Sumber Daya Manusia yang Unggul di Era Kontemporer) - Mila Mutiara Choirunisa; Nur Saidah (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
At the beginning of the 20th century, Islamic education in Indonesia was separated between religious and general knowledge. K.H. Ahmad Dahlan, the founder of Muhammadiyah, emerged as a reformer with a vision of integrating these two fields in a modern education system. This research explores the educational methodology of K.H. Ahmad Dahlan and his relevance in the contemporary era, using qualitative descriptive methods with literature studies from various secondary sources. The research results show that K.H.'s educational approach. Ahmad Dahlan, who combined religious values ​​with general knowledge, succeeded in changing the paradigm of Islamic education in Indonesia. This approach improves the intellectual quality as well as the spiritual and moral aspects of students. Through Muhammadiyah, K.H. Ahmad Dahlan founded educational institutions that play an important role in empowering Muslims and national education. In conclusion, the educational contribution of K.H. Ahmad Dahlan through Muhammadiyah has had a significant and sustainable impact. The educational methodology he applies remains relevant and can be used as a model in the development of Islamic education today. Therefore, it is important to continue to study and apply his thinking in the current educational context in order to face today's challenges.